Analisa Kualitas Susu Kambing Peranakan Etawah yang Disterilkan pada Suhu dan Waktu yang Berbeda - Yusdar Zakaria; Helmi M. Yahya; Yuda Safara (Agricultural Faculty, 2011)
Analyze of Etawas milk goat quality sterilized at the Different Temperature and TimeABSTRACT. The objective of this experiment is to study the quality of sterilization of etawas goat milk at different temperature (110oC and 120oC) and different time (3 second and 6 second). The quality of sterilization of etawas goat milk was evaluated by measuring crude protein, crude fat, pH value and amount of microorganism. The study used a factorial completely randomizes design. The result showed that the different temperature and time of sterilized goat milk have not significant (P0,05) on crude protein, crude fat, pH value and amount of microorganism. The result also showed that no interaction between temperature and time. The conclusion of the research indicated that all the experiment have the same quality.